Recommendation for validation and quality assurance of non-invasive prenatal testing for foetal blood groups and implications for IVD risk classification according to EU regulations - Banch Clausen, Frederik; Hellberg, Åsa; Bein, Gregor; Bugert, Peter; Schwartz, Dieter; Drnovsek, Tadeja Dovc; Finning, Kirstin; Guz, Katarzyna; Haimila, Katri; Henny, Christine; O'Brien, Helen; Orzinska, Agnieszka; et al. (Vox sanguinis, 2022)
Background and Objectives Non-invasive assays for predicting foetal blood group status in pregnancy serve as valuable clinical tools in the management of pregnancies at risk of detrimental consequences due to blood group antigen incompatibility. To secure clinical applicability, assays for non-invasive prenatal testing of foetal blood groups need to follow strict rules for validation and quality assurance. Here, we present a multi-national position paper with specific recommendations for validation and quality assurance for such assays and discuss their risk classification according to EU regulations. Materials and Methods We reviewed the literature covering validation for in-vitro diagnostic (IVD) assays in general and for non-invasive foetal RHD genotyping in particular. Recommendations were based on the result of discussions between co-authors. Results In relation to Annex VIII of the In-Vitro-Diagnostic Medical Device Regulation 2017/746 of the European Parliament and the Council, assays for non-invasive prenatal testing of foetal blood groups are risk class D devices. In our opinion, screening for targeted anti-D prophylaxis for non-immunized RhD negative women should be placed under risk class C. To ensure high quality of non-invasive foetal blood group assays within and beyond the European Union, we present specific recommendations for validation and quality assurance in terms of analytical detection limit, range and linearity, precision, robustness, pre-analytics and use of controls in routine testing. With respect to immunized women, different requirements for validation and IVD risk classification are discussed. Conclusion These recommendations should be followed to ensure appropriate assay performance and applicability for clinical use of both commercial and in-house assays.
First published: 21 June 2021
Gesehen am 01.09.2023